2014
DOI: 10.3109/03008207.2014.923878
|View full text |Cite
|
Sign up to set email alerts
|

Bone-specific overexpression of DMP1 influences osteogenic gene expression during endochondral and intramembranous ossification

Abstract: Dentin matrix protein 1 (DMP1) is a key regulator for osteoblast differentiation and mineralization of the bone extracellular matrix (ECM). Osteocalcin (OCN) is one of the most abundantly expressed non-collagenous protein by osteoblasts in bone. In the present study, we generated a mouse model (OCN-DMP1) that overexpresses full-length DMP1 utilizing the OCN promoter. Expression of genes encoding osteogenic transcription factors and ECM proteins during early post-natal development in male OC-DMP1 and wild type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…This is also in line with a study performed by Gandavarapu et al, who used thiolene chemistry to functionalize poly(ethylene glycol) hydrogels with a pendant peptide moiety and found that stiffer gels with Young’s modulus of 25 kPa had increased ALP activity on day 14 than the softer hydrogels with a modulus of 2 kPa [46]. Furthermore, OCN is the most abundant non-collagenous protein in bone extracellular matrix [47] and its expression is closely related to bone metabolism including bone extracellular matrix mineralization and turnover [48]. Figure 4 demonstrates the results of OCN assay on different composites.…”
Section: Discussionsupporting
confidence: 85%
“…This is also in line with a study performed by Gandavarapu et al, who used thiolene chemistry to functionalize poly(ethylene glycol) hydrogels with a pendant peptide moiety and found that stiffer gels with Young’s modulus of 25 kPa had increased ALP activity on day 14 than the softer hydrogels with a modulus of 2 kPa [46]. Furthermore, OCN is the most abundant non-collagenous protein in bone extracellular matrix [47] and its expression is closely related to bone metabolism including bone extracellular matrix mineralization and turnover [48]. Figure 4 demonstrates the results of OCN assay on different composites.…”
Section: Discussionsupporting
confidence: 85%
“…Dentin Matrix Protein 1 (DMP1) is a bone-specific important marker for osteocyte formation and phosphate metabolism for maintaining mineralization of the bone extracellular matrix. Mutation on DMP1 gene could cause abnormalities in bone development, such as osteomalcia and rickets [47,48]. Whereas, osteocalcin (OCN) plays its role when precursor cells committed to differentiate into mature osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…68 This gene is involved in osteoblast differentiation, and the protein DMP-1 is critical for proper mineralization of bone ECM. 69 Interestingly, our findings suggest that the hydrogel alone (i.e., without BMP-2) exhibits a greater osteocytic phenotype. Contrarily, the presence of BMP-2 in this hydrogel system appears to retain the MC3T3-E1 differentiation closer to an osteoblastic phenotype, ECM.…”
Section: ■ Materials and Methodsmentioning
confidence: 66%